2019
DOI: 10.1101/528166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative identification of microRNAs inApis cerana ceranaworkers’ midguts responding toNosema ceranaeinvasion

Abstract: 30 MicroRNAs (miRNAs) are endogenous small noncoding RNAs that post 31 transcriptionally regulate gene expression and are involved in many biological 32 processes including host-pathogen interactions. However, the potential role of 33 miRNAs in the responses of eastern honeybees to Nosema ceranae invasion is 34 completely unknown. Here, the expression profiles and differentially expressed 35 miRNAs (DEmiRNAs) in the midguts of Apis cerana cerana workers 7 and 10 days 36 post infection (dpi) with N. ceranae wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…1C). The shared miRNA profile is from normal and N. ceranae -infected midguts of A. c. cerana workers [1]. On average, more than 12.54 Mb raw reads in each group were yielded from sRNA-seq, and over 12.02 Mb (95.83%) clean reads were gained after strict filtering and quality control (Table 1).…”
Section: Datamentioning
confidence: 84%
See 2 more Smart Citations
“…1C). The shared miRNA profile is from normal and N. ceranae -infected midguts of A. c. cerana workers [1]. On average, more than 12.54 Mb raw reads in each group were yielded from sRNA-seq, and over 12.02 Mb (95.83%) clean reads were gained after strict filtering and quality control (Table 1).…”
Section: Datamentioning
confidence: 84%
“…Small RNA libraries were constructed according to the general protocol [1]. Briefly, total RNA of each midgut sample in N. ceranae -treated and control groups were extracted using TRIzol Reagent followed by removal of DNA contaminants; only values of 28S/18S ≥ 0.7 and RIN ≥7.0 were considered qualified for the subsequent small RNA library construction.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculation and rearing of A. c. cerana workers as well as midgut sample preparation were performed according to the established procedure in our lab [4, 5]. Briefly, (1) To offer newly emerged Nosema-free workers, combs of sealed brood from a healthy colony were kept in an incubator at 34 ± 0.5 °C, 50% RH; the emergent workers were seriously transferred into cages in groups (n=35) and kept in the incubator at 32 ± 0.5 °C, 50% RH.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small noncoding RNAs of approximately 22 nt in length, which regulate gene expression at the post-transcriptional level by targeting sites in mRNA, and have been shown to regulate a variety of physiological processes throughout insect development [4]. Up to date, thousands of miRNAs have been identi ed from insect species, including Drosophila melanogaster [5], Bombyx mori [6,7], Locusta migratoria [8], Manduca sexta [9][10][11], Plutella xylostella [12,13], Helicoverpa armigera [14,15], Mayetiola destructor [16], Nilaparvata lugens [17], Blattella germanica [18], Aphis gossypii [19], Lissorhoptrus oryzophilus [20], Leptinotarsa decemlineata [21], Grapholita molesta [22], Atrijuglans hetaohei [23], Apis cerana cerana [24], Laodelphax striatellus [25], and Plodia interpunctella [26]. More recent evidence has shown that miRNAs may play an important role in regulation of insect diapause.…”
Section: Introductionmentioning
confidence: 99%